Medical Cost Analysis of the Osteoporotic Hip Fractures - Savaş Çamur; Bekir Eray Kılınç; Mehmet Mesut Sönmez; Haluk Çelik; Yunus Öç (Galenos Yayinevi, 2015)
Objective: Osteoporotic hip fractures decrease the life expectancy for 20% about 20-50% of the patients become permanently dependent in terms of walking for the rest of their life. Life expectancy is increasing in Turkey in the last 20 years. We investigated the impact of osteoporotic hip fractures which increase the morbidity and mortality on the national economy. Materials and Methods: A total of 81 patients admitted to our emergency department with the diagnosis of femur intertrochanteric fracture and femoral neck fracture between 2008 and 2012 were included in this study. We retrospectively evaluated the medical records and the medical costs of these patients from hospital information management system. Results: Of the 81 patients 32 (39.6%) males and 49 (60.4%) females meeting the inclusion criteria were included in this study. The mean age was 80.1 years (range, 61-103). Twenty-three (27.5%) patients had femoral neck fracture and 58 (72.5%) patients had intertrochanteric femur fracture. The mean length of hospital stay was 13.4 days in intertrochanteric femur fracture and 15.5 days in femoral neck fracture; average of the total days of hospitalization of all patients was 13.9 days. The average treatment cost per patient was 5,912.36 TL for intertrochanteric fractures, 5,753.00 TL for neck fractures, and 5,863.09 TL for the whole patient population. Conclusion: Hip fracture is a substantial cause of morbidity and mortality in elderly. Taking preventive measures before the fracture occurs may help to prevent this problem which has a high cost treatment and which is a substantial burden for the national economy.